Pituitary Apoplexy Causing Compression of Third Cranial Nerve—Management - Masopust, Václav (Indian Journal of Neurosurgery, 2019)
Lesions of the oculomotor nerve as the first sign of pituitary adenoma are rare. The cause of such lesions without other clinical symptoms is discussed in this study. A small cohort of 4 patients (3.1%) with oculomotor nerve palsy (third nerve palsy) as the only neurologic deficit, from 129 patients who got operated upon for pituitary adenomas, is presented. In this group (mean age: 55 years, range: 36–65 years), all patients (two women and two men) underwent surgery. In two cases, there was arrested pneumatization and thickened bone. In the remaining two cases, a macroscopically visible, very solid opaque diaphragm was present, after the removal of the tumor and thickened bone. Complete adjustment was observed in all patients within 1 week after the surgery. Two factors that seem to increase the high risk for the development of oculomotor nerve palsy are that the cavernous sinus may be the only weak structure surrounding the sella turcica when the diaphragm and bone are thickened; and the rapid development of increased pressure in this region. The increased pressure on the cavernous sinus during the anatomical variations is the primary cause for lesions on the oculomotor nerve. However, this conjecture cannot be statistically demonstrated because of the small number of cases. Future research should be conducted on larger samples to increase statistical inference and generalizability.
Keywords: pituitary apoplexy; oculomotor nerve; anatomical variations; sella turcica